A diamagnetic iron complex and its twisted sister – structural evidence on partial spin state change in a crystalline iron complex. Issue 43 (28th October 2021) - Salojärvi, Esko; Peuronen, Anssi; Moilanen, Jani; Huhtinen, Hannu; Lindén, Johan; Mansikkamäki, Akseli; Lastusaari, Mika; Lehtonen, Ari
Abstract : Diamagnetic Fe complex was made of a redox non-innocent ligand precursor  N, N ′-bis(3, 5-di- tert -butyl-2-hydroxy-phenyl)-1, 2-phenylene-diamine and FeCl3 . Its phenoxazine derivative was obtained via intra-ligand cyclisation of the parent complex. Abstract : We report here the syntheses of a diamagnetic Fe complex [Fe(HL)2 ] (1 ), prepared by reacting a redox non-innocent ligand precursor N, N ′-bis(3, 5-di- tert -butyl-2-hydroxy-phenyl)-1, 2-phenylenediamine (H4 L) with FeCl3, and its phenoxazine derivative [Fe(L′)2 ] (2 ), which was obtained via intra-ligand cyclisation of the parent complex. Magnetic measurements, accompanied by spectroscopic, structural and computational analyses show that 1 can be viewed as a rather unusual Fe(iii ) complex with a diamagnetic ground state in the studied temperature range due to a strong antiferromagnetic coupling between the low-spin Fe(iii ) ion and a radical ligand. For a paramagnetic high-spin Fe(ii ) complex 2 it was found that, when crystalline, it undergoes a thermally induced process where 25% of the molecules in the material change to a diamagnetic low-spin ground state below 100 K. Single crystal X-ray studies conducted at 95 K afforded detailed structural evidence for this partial change of spin state of 2 showing the existence of crystallographically distinct molecules in a 3 : 1 ratio which exist in high- and low-spin states, respectively. Also, the magnetic behaviour of 2 was found to be related with the crystallinity of the material as demonstrated by near-IR radiation to unpaired electrons conversion ability of amorphous sample of 2 .